Analisis Putusan Mahkamah Konstitusi Nomor 40/PUU-XXIV/2026 Tentang Pemisahan Anggaran Pendidikan Dan Program Makan Bergizi Gratis - Mutiara Deja Saputri; Pipi Susanti (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Constitutional Court Decision Number 40/PUU-XXIV/2026 concerning the separation of education funding and the Free Nutritious Meals Program (MBG) raises questions regarding the limits of authority of the Constitutional Court, the President, and the House of Representatives in budgetary policy. This study aims to analyze the Constitutional Court’s authority in reviewing budgetary policies and the implications of the decision for the authority of the President and the House of Representatives. This research employs normative legal research using statutory, conceptual, and case approaches. The results show that the Constitutional Court has the authority to review the constitutionality of provisions in the State Budget Law but may not assume the authority of the President and the House of Representatives in determining budgetary policies. Decision Number 40/PUU-XXIV/2026 limits the inclusion of MBG funding that does not constitute a main component of education within the 20% education budget and requires its separation no later than the 2028 State Budget. Thus, the President and the House of Representatives retain their authority to determine budgetary policies within the constitutional boundaries established by the Constitutional Court.